KONTEKTUALISASI MANAGEMENT INVENTORY PANGAN NASIONAL DALAM PERSPEKTIF ISLAM - Hakim, Maman Rahman (IBN KHALDUN BOGOR, 2015)
The basic value of food security is the availability of food stocks and accessibility. Ironically, the increased production of food commodities in Indonesia is not matched with the proper stock management system, so as if Indonesia is experiencing a food crisis in the commodity. Institutional food stock management national scale in Indonesia there are at least two that Bulog and the Warehouse Receipt System. Qur'an as the Muslim holy book always irrelevant to solving the problems of social. To that end, the presence of the Koran to be the solution to provide instructions and guidance of life, one of them about food security problems associated with foodstock management. In this paper will discuss how national institutional stock management in Indonesia, and how to contextualise the concept of national food stock management in the perspective of Islam. From both expected to provide a solution to the problem of food stock management in Indonesia